CIMMYT scientists deliver training to improve agriculture in Uzbekistan - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
Agricultural scientists from Uzbekistan completed training on genetic resources and gene banks in Türkiye to build research cooperation and enhance agricultural knowledge across the region.